Alcohol's effects on the mouse brain are modulated by age and sex. (12th July 2022) - Piekarski, David J.; Zahr, Natalie M.; Zhao, Qingyu; Sullivan, Edith V.; Pfefferbaum, Adolf
Abstract: Binge alcohol consumption is common among adolescents and may impair normal brain development. Emerging, longitudinal studies in adolescents suggest that the effects of binge alcohol exposure on brain structure differ between sexes. To test the hypothesis that the effects of binge alcohol exposure on developmental brain growth trajectories are influenced by age of exposure and sex, adolescent and adult, male and female C57Bl/6 mice ( n = 32), were exposed to a binge‐like ethanol (EtOH) exposure paradigm (i.e., 5 cycles of 2 on/2 off days of 5 g/kg EtOH intraperitoneal) or served as saline controls. Longitudinal structural magnetic resonance imaging was acquired at baseline, following binge EtOH exposure, and after 2 weeks of recovery. Alcohol treatment showed interactions with age and sex in altering whole brain volume: adolescents of both sexes demonstrated inhibited whole brain growth relative to their control counterparts, although significance was only attained in female mice which showed a larger magnitude response to EtOH compared to male mice. In region of interest analyses, the somatosensory cortex and cerebellum showed inhibited growth in male and female adolescent mice exposed to EtOH, but the difference relative to controls did not reach multiple comparison‐corrected statistical significance. These data suggest that in mice exposed to binge EtOH treatment, adolescent age of exposure and female sex may confer a higher risk to the detrimental effects of EtOH on brain structure and reinforce the need for direct testing of both sexes. Abstract : Sex and age may influence the brain's vulnerability to binge alcohol exposure. Here, we find that age and sex interact to influence alcohol‐induced whole brain volume measures with adolescent female mice at heightened vulnerability compared to other groups of mice. The cerebellar and somatosensory cortices were affected, demonstrating that age and sex influence global and region brain volumes in mice.